Reinforcement Learning in AI-Driven Assessments : Enhancing Continuous Learning and Accessibility - Vijay Kumar Valaboju, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article explores the transformative potential of Reinforcement Learning (RL) in AI-driven assessments, examining its impact on personalized learning experiences and continuous skill development. We investigate how RL algorithms enable adaptive learning systems to create dynamic, individualized learning paths, provide real-time feedback, and optimize long-term educational outcomes. The article delves into key aspects such as personalized learning trajectories, adaptive difficulty adjustments, and the integration of gamification elements to enhance engagement. We discuss the application of these technologies in various contexts, from traditional educational settings to professional development and certification preparation. The article also addresses the challenges and limitations of implementing RL in educational technology, including concerns about algorithmic bias and the complexity of modeling human learning processes. By analyzing current research and potential future directions, this paper provides a comprehensive overview of how RL is reshaping the landscape of education and assessment, offering insights into the future of adaptive learning systems and their role in fostering lifelong learning in an increasingly digital world.
Keywords: Reinforcement Learning; Adaptive Assessment; Personalized Learning; AI-driven Education; Cognitive Load Management